2004
DOI: 10.1002/macp.200300118
|View full text |Cite
|
Sign up to set email alerts
|

Retarded Anionic Polymerization: Copolymerization of Butadiene and Styrene in the Presence of Alkyllithium and n,s‐Dibutylmagnesium or Triisobutylaluminium Derivatives

Abstract: Summary: The influence of Lewis acid additives on the anionic butadiene polymerization using lithium as a counter ion in non‐polar solvent is investigated. A decrease of the polymerization rate was always observed. In the presence of n,s‐Bu2Mg the percentage of 1,2‐vinyl units increases with the [Mg]/[Li] ratio. This evolution can be explained by further complexation of lithium with free dialkylmagnesium modifying the nature of the propagating species and/or possible 1,4 to 1,2 isomerization during chain excha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2006
2006
2022
2022

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 13 publications
(5 citation statements)
references
References 16 publications
0
5
0
Order By: Relevance
“…We have shown recently that the association of organoaluminic derivatives (AlR y X 3- y ) to alkali metal salts yield the formation of “ate” complexes which are active initiators both for the retarded anionic polymerization of styrenic monomers and dienes , and for the anionic polymerization of propylene oxide (POx). , For the oxirane, in contrast to ethylenic monomers, a slight excess of the aluminum derivative with respect to the alkali metal is needed to trigger the polymerization. This is explained by the necessary formation of a second complex between the aluminum derivative in excess and the monomer.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…We have shown recently that the association of organoaluminic derivatives (AlR y X 3- y ) to alkali metal salts yield the formation of “ate” complexes which are active initiators both for the retarded anionic polymerization of styrenic monomers and dienes , and for the anionic polymerization of propylene oxide (POx). , For the oxirane, in contrast to ethylenic monomers, a slight excess of the aluminum derivative with respect to the alkali metal is needed to trigger the polymerization. This is explained by the necessary formation of a second complex between the aluminum derivative in excess and the monomer.…”
Section: Introductionmentioning
confidence: 99%
“…11 However, Esswein and Mo ¨ller showed that the addition of strong Lewis base, for example the phosphazene base tBu-P 4 , can strongly complex the Li + counterion and allows EO polymerization in THF. [12][13][14] We have shown recently that the association of organoaluminic derivatives (AlR y X 3-y ) to alkali metal salts yield the formation of "ate" complexes which are active initiators both for the retarded anionic polymerization of styrenic monomers and dienes 15,16 and for the anionic polymerization of propylene oxide (POx). 17,18 For the oxirane, in contrast to ethylenic monomers, a slight excess of the aluminum derivative with respect to the alkali metal is needed to trigger the polymerization.…”
Section: Introductionmentioning
confidence: 99%
“…Finally, it should be noted that some authors propose an 1,4‐3,4 isomerization to explain the regioselectivity changes observed in the course of an alkyl lithium mediated anionic polymerization of diene conducted in the presence of magnesium dialkyls 41, 42…”
Section: Discussionmentioning
confidence: 99%
“…For instance, polar modifiers and retarders have been investigated for the polybutadiene system [ 35 ] and for polyisoprene. [ 36–41 ] In brief, previous studies revealed an increase of the 1,2 addition instead of the 1,4 diene addition mode with increasing content of polar modifier. [ 42 ] The microstructures and the content of possible 1,2‐, 3,4‐ and 1,4‐ polymyrcene units ( Figure ) were determined by 1 H NMR spectroscopy.…”
Section: Methodsmentioning
confidence: 99%